Adhesion mechanisms and mechanical performance of single-lap joints in FDM-3D printed: A review - Muhamad Qeisya Hanif; Rifelino Rifelino; Febri Prasetya; Zainal Abadi (Researcher and Lecturer Society, 2026)
Additive Manufacturing (AM), particularly Fused Deposition Modeling (FDM), has evolved from a rapid prototyping technology into a manufacturing approach for producing functional components across a wide range of industrial sectors. Nevertheless, the limited build volume of FDM systems has encouraged the use of adhesive bonding as a practical method for joining sub-components, with the single-lap joint (SLJ) configuration being among the most widely adopted designs. This review aims to provide an integrated analysis of the relationship between FDM-induced surface morphology, the adhesion mechanisms developed at the bonded interface, and their implications for stress distribution, shear strength, and joint failure modes. The findings indicate that the surface characteristics generated by the FDM process, including layer lines, stair-stepping effects, voids, and porosity, create interfacial conditions that differ fundamentally from those of homogeneous materials. These characteristics also produce a non-linear relationship between surface roughness and joint strength. Process parameters such as printing orientation and layer height were identified as key controlling factors that influence surface topography and adhesive performance. From a mechanical perspective, the eccentric load path inherent in SLJ configurations generates significant shear and peel stress concentrations at the overlap ends. These stress concentrations coincide with structurally weak regions that are intrinsically associated with FDM adherends, making them the primary sites for crack initiation and joint failure. Furthermore, modifications to overlap geometry and tailored adhesive distribution have been recognized as effective strategies for improving stress redistribution and enhancing the load-bearing capacity of the joint. This review highlights that the assessment of adhesive joints in FDM-manufactured components requires an integrated analytical framework that accounts for the coupled interactions among printing process parameters, surface conditions, adhesive properties, and progressive failure modeling. Such an approach is essential for the development of reliable structural joint designs for FDM-based applications.